2005
DOI: 10.1007/s00442-005-0028-1
|View full text |Cite
|
Sign up to set email alerts
|

Examining the strength and possible causes of the relationship between fire history and Sudden Oak Death

Abstract: Fire can be a dominant process in the ecology of forest vegetation and can also affect forest disease dynamics. Little is known about the relationship between fire and an emerging disease epidemic called Sudden Oak Death, which is caused by a new pathogen, Phytophthora ramorum. This disease has spread across a large, fire-prone portion of California, killing great numbers of oaks and tanoaks and infecting most associated woody plants. Suitable hosts cover a much broader geographic range, raising concern over w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 50 publications
3
25
0
Order By: Relevance
“…This agrees with two recent studies that observed greater levels of P. ramorum infection in locations with higher abundance of the foliar host bay laurel (Maloney et al 2005, Condeso andMeentemeyer 2007). Likewise, Moritz and Odion (2005) suggested that succession toward higher host densities in the absence of fire could cause a relationship between time since fire and P. ramorum presence. Second, we found that higher densities of trees reduce maximum daily understory temperatures.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This agrees with two recent studies that observed greater levels of P. ramorum infection in locations with higher abundance of the foliar host bay laurel (Maloney et al 2005, Condeso andMeentemeyer 2007). Likewise, Moritz and Odion (2005) suggested that succession toward higher host densities in the absence of fire could cause a relationship between time since fire and P. ramorum presence. Second, we found that higher densities of trees reduce maximum daily understory temperatures.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, mechanical thinning of bay laurel vegetation may be an even more effective way of reducing inoculum pressure in forest understories . Ultimately, more research is needed to understand the efficacy of possible management solutions that can be applied at landscape to regional scales and the potential for unintended ecological consequences of prescribed fire or vegetation thinning in woodland ecosystems (Moritz andOdion 2005, Rizzo et al 2005). Prior to application of such management activities at broad spatial scales, small-scale manipulative experiments are needed to reveal which types of treatments may be most effective at limiting disease transmission and persistence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was little indication that changes in community composition could be reversed, owing to a reduction in juvenile survivorship and the high proportion of existing resprouters that were diseased. Because time since fire can be a strong driver of ecosystem structure and species composition, Moritz and Odion (2005) hypothesised that certain successional stages will be more prone to infection than are others. Therefore, future management of recurring fires and soil-borne disease may mediate stability, or continuing decline, of susceptible species.…”
Section: Discussionmentioning
confidence: 99%
“…These factors may also affect survival or virulence of any soil-borne pathogen; however, little is known of the effect of fire on pathogens, such as Phytophthora spp., and their interaction with the host after fire. Fire can affect disease activity by directly affecting the pathogen's survival and development (Weste 1974;Schwartz et al 1995;Moritz and Odion 2005) or, indirectly, by affecting the plant (Marks et al 1975) and/or microbial community (Treseder et al 2004) or the physical environment (Podger and Brown 1989;Shearer and Tippett 1989;Bishop et al 2010). Furthermore, plants stressed by fire, low nutrients, drought or defoliation are more likely to succumb to disease (Schoeneweiss 1975).…”
Section: Introductionmentioning
confidence: 99%